Costing participation in sport : the best option dilemma of a student-athlete - Alcorn, Michael, active 2023; Abeza, Gashaw; O'Reilly, Norm, 1973- (London : Human Kinetics, Inc., 2022)
This case discusses the dilemma that the student athlete is facing in choosing the best option. Speciﬁcally, the case outlines different factors that student athletes are facing in looking to transition to elite performance. Students are asked to assume the perspective of Rebecca Grifﬁn, a university varsity rower. Rebecca is in the process of assessing and considering the beneﬁts and drawbacks of her summer rowing club options. The considerations include club registration fees, travel, equipment, coaching, and competition entry costs for each and how they will contribute to her career goals in rowing. Therefore, while working toward her goals, Rebecca needs to consider the affordability of her options and solve the best option dilemma that she has faced. The scenario presented by this case is one that many collegiate athletes ﬁnd themselves in when they need to decide where they plan to live and train over the summer. Background is provided pertaining to three rowing clubs that she is considering and the pros and cons of choosing any of those three clubs. Information is also included on multiple regional championship competitions, which Rebecca must consider in addition to the monetary costs as this information pertains to the potential competitiveness of Rebecca's summer rowing. Students are asked to put themselves in the place of Rebecca and justify any choice that they would be making.
Description based on XML content.
Keywords: elektronické knihy; electronic books; College athletes -- Economic conditions -- Case studies; Sports -- Economic aspects -- Case studies; Sports -- Costs -- Case studies; Sports -- Finance -- Case studies; Dilemma -- Case studies